Coating of 2-Aminobenzimidiazole and 1-(o-Tolyl)biguanide Functionalized Silicas on Iron Sand Magnetic Material for Sorption of [AuCl4]– - Nuryono Nuryono; Nur Mutia Rosiati; Abraham L Rettob; Suyanta Suyanta; Yateman Arryanto (Indonesian Journal of Chemistry, 2019)
Two novel materials of 2-aminobenzimidiazole (AB) and 1-(o-tolyl)biguanide (TB) modified silicas coated on the iron sand magnetic material (MM@SiO2/AB and MM@SiO2/TB) have been synthesized and were used to adsorb Au(III) from Au/Cu/Ni solution. Silica layering MM was modified with polyamino compounds via a sol-gel process using a sodium silicate solution, 3-chloropropyltrimethoxysilane (CPTS) and modifier compounds. Adsorption of Au(III) on MM@SiO2/AB and MM@SiO2/TB was investigated in a batch system by varying pH, initial concentration, contact time and the presence of other metal ions (Cu(II) and Ni(II)). The results showed that MM@SiO2/AB and MM@SiO2/TB were successfully synthesized through the sol-gel process using cross-linking agent CPTS. Adsorption of Au(III) on MM@SiO2/AB and MM@SiO2/TB decreased with the increase of pH and followed the Langmuir isotherm models with adsorption capacity of 17.15 and 9.44 mg/g, respectively. The adsorption kinetics fit to pseudo-second-order model with the rate constants of 1.16 × 10-2 and 1.46 × 10-2 g mg-1 min-1, respectively. MM@SiO2/AB and MM@SiO2/TB gave a high selectivity towards Au(III) in a mixture of Cu(II) and Ni(II). The desorption using thiourea 1 M solution in 1 M HCl of metal ions showed that percentage of Au(III) desorbed was higher than that of Cu(II) and Ni(II).